REPRESENTATIONS OF MEXICO CITY IN THE CHRONICLE (Andamios, Revista de Investigación Social, 2004)
In this work a summary of the history of the chronicle is made and it is used as leitmotiv some treatments of those that has been object the city of Mexico, some of its representations they are underlined in columnists and authors that have treated her. It is to relate how the city has been narrated and imagined by some of its columnists and writers.